Pendampingan Bagi Guru Dalam Merancang Pembelajaran Berdiferensiasi Berbasis Teknologi Informasi Di SD Negeri 144 Pekanbaru - Lingga, Leny Julia; Dafit, Febrina; Jatra, Rices; Sakila, Nesa; Utami, Nurul Cahya (Universitas Pahlawan Tuanku Tambusai, 2025)
Differentiated learning is one of the approaches in the Merdeka Curriculum, emphasizing the diversity of students' learning needs. However, observations and interviews indicate that many teachers at SD Negeri 144 Pekanbaru still face difficulties in designing and implementing differentiated learning based on information technology. The main challenges include limited understanding of teaching modules, lack of comprehensive training, and minimal use of technology in the learning process. Therefore, this mentoring program aims to enhance teachers' understanding and skills in designing teaching modules aligned with differentiated learning principles while integrating information technology into the learning process. The methods used in this program include socialization, training, technology application, direct mentoring, and evaluation to ensure program sustainability. The results indicate a significant improvement in teachers' understanding and ability to design and implement technology-based teaching modules. Additionally, teachers can integrate various digital platforms to support more interactive and student-centered learning. In conclusion, this mentoring program positively impacts teachers' competencies and is expected to contribute to improving the quality of education in elementary schools.